Il sogno di Alice - Beseghi, Emma (Studi sulla Formazione/Open Journal of Education, 2017)
Alice in Wonderland, published in 1865, is 150 years old and continues to be one of the most popular masterpieces that is appreciated by children and adults. The article explores the polysemy of the text, its fine hermeneutical approaches, the symbolic ramifications of its visual reinterpretations – especially in the illustra-tions. This novel continues to fuel our imagery and, at same time, it continues to discuss the biographers of Carroll on the complex personality of this author. In particular, the article emphasizes the original and unexpected turn that Alice in Wonderland gave to children’s literature, through the storytelling of a point of view – “another look” – that definitely belongs to childhood.